Selectivity of the Formation of the Ring-Closed Products and Methylcyclohexenes in the Dehydrogenation of Methylcyclohexane to Toluene. (10th July 2012) - Usman, Muhammad R.; Cresswell, David L.; Garforth, Arthur A.
Abstract : In our previous publication (Usman et al., 2011), the by-products formation during the dehydrogenation of methylcyclohexane over 1.0 wt% Pt/ γ -Al2 O3 was studied under wide range of operating conditions. The formation and yield patterns of benzene, cyclohexane, and isomers of xylene were studied. In the present contribution, the formation and yield patterns of the ring-closed products (sum of ethylcyclopentane and dimethylcyclopentanes) and methylcyclohexenes are studied. The yields of both of the ring-closed products (RCPs) and methylcyclohexenes (MCHes) were observed to increase with an increase in pressure. However, the effect of hydrogen concentration was found affecting differently at the low and at the high pressures. The yield patterns of methylcyclohexenes suggested methylcyclohexenes as the reaction intermediate in the formation of toluene.